Model Development Study of Historical Object for Non-Education Program History - Rudy Gunawan (Intelektual Pustaka Media Utama, 2016)
Study of historical objects in the beginning is one of the subjects in the study program of the Faculty of History Teaching and Education University of Muhammadiyah Prof. Dr. Hamka Jakarta. But then became subjects featured because every student can immediately know the attractions and historical objects that have just exist in books or on the internet. The experience gained by the students not only knowledge but more important is the emergence of a sense of love and pride for the historical objects visited and implications for the love of the homeland Indonesia. Besides visiting historical object, also conducted comparative studies with historical education courses that are in the city to share experiences and exchange ideas on the development of education courses in Indonesian history. Therefore, the study of the historical objects need to be developed not only involves students of history education but also students from other courses, so as to form the character of patriotism in all students.